A problem of multiple drug overdose by patient with schizophrenia - case report - Orzeł, Anna Katarzyna; Klatka, Barbara; Janeczko, Dominika; Hołowczuk, Magdalena; Terpiłowski, Michał; Tchórz, Michał (Journal of Education, Health and Sport, 2019)
IntroductionSuicidal risk caused by drug overdose is a considerable factor influencing earlier mortality among people with schizophrenia. An adjustment of effective pharmacological treatment is essential to sustain the stability of the patient. Commonly, the treatment divides to two groups: first generation antipsychotics (FGA) and second-generation antipsychotics (SGA). Yet, due to significant risk of depression and possible side effects of the drugs, other medicaments should also be introduced.Case reportA 38 years old woman that was repeatedly hospitalized at the local ward, brought by ambulance and admitted to the Clinical Toxicology Department. She was admitted to the department for 20th time in period between April 2013 and May 2019 due to deliberate drug overdoses. During last hospitalization laboratory tests indicated presence of valproic acid (121,41 μg/ml). Moreover, psychiatric consultation revealed that although she was balanced state, she was not critical about her behavior. Patient was diagnosed with schizophrenia and mild intellectual disability. Each time, the intoxication was followed by medications from group of antipsychotics and tranquilizers used in treatment of the illness. Additionally, she confirmed that some of intoxications had suicidal attempt. 60% of hospitalizations of the patient were followed by stay in Neuropsychiatric hospital for further observation and treatment.ConclusionThe administration of proper dosage of antipsychotics should be precisely controlled by the psychiatrist that takes care of the patient. For patients with greater suicidal risk, SGA are more recommended than FGA. Moreover, drugs from other groups such as antidepressants should also be introduced. Undoubtedly, efficient pharmacological treatment should be supported by psychotherapy of the patient.